Promising Applications of Nanoparticles in the Treatment of Hearing Loss - Huang, Zilin; Xie, Qiang; Li, Shuang; Zhou, Yuhao; He, Zuhong; Lin, Kun; Yang, Minlan; Song, Peng; Chen, Xiong (Frontiers in Cell and Developmental Biology, 2021)
Hearing loss is one of the most common disabilities affecting both children and adults worldwide. However, traditional treatment of hearing loss has some limitations, particularly in terms of drug delivery system as well as diagnosis of ear imaging. The Blood-labyrinth barrier (BLB) , the barrier between the vasculature and fluids of the inner ear, restricts entry of most blood-borne compounds into inner ear tissues. Nanoparticles (NPs) have been demonstrated high biocompatibility, good degradation and simple synthesis process in the process of diagnosis and treatment, which are promising for medical applications in hearing loss. Although previous studies have showed that nanoparticles have a good application prospect in the field of inner ear diseases, there is still a gap between biological research and clinical application. In this paper, we aim to summarize developments and challenges of nanoparticles in diagnostics and treatment of hearing loss in recent years. This review may be useful to raise otology researchers’ awareness of effect of nanoparticles on hearing diagnosis and treatment.